Point of Sales Application Development at Worm Store Workshop - Davit Hermawan; Yayat Sutrayana; Abudiman (Institute of Computer Science (IOCS), 2022)
Workshop/Mobile Store Worms Store is a store that sells various brands of Mobile. This shop has been established for 5 years and continues to grow until now. Unfortunately, this development is not followed by developments in the store's sales and marketing system. Incoming data collection system used for this still use the application of data processing manually that is using handwritten in bookkeeping. It is considered less effective and efficient in supporting the productivity of employees in it. From the problem raises the idea to create a web-based application, Customer Relationship Management (CRM) is integrated with point of sales. The methodology used in making this application is Spiral method. The programming language is PHP and HTML. To view using CSS and Jquery. The database uses MySQL. Tools and Editor used is XAMPP for Windows, Photoshop, Sublime text 3. With the application of Point of Sales Web-Based is expected to facilitate administrators in managing the goods so that the results of reporting data can be known easily, quickly and accurately.